Effect of sintering temperature on structural and morphological properties of europium (III) oxide doped willemite - Nur Fatin Syamimi; Matori, Khamirul Amin; Lim, Way Foong; Abdul Aziz, Sidek; Mohd Zaid, Mohd Hafiz (Hindawi Limited, 2015)
Willemite- (Zn2SiO4-) based glass ceramics doped with various amounts of europium oxide (Eu2O3) were prepared by solid state melting and quenching method. Effect of sintering temperature (600–1000∘ C) on structural and morphological properties of the doped samples was investigated. Phase composition, phase evolution, functional groups, and microstructure analysis were, respectively, characterized using X-ray diffractometer (XRD), fourier transform infrared spectroscopy, field emission scanning electron microscopy (FE-SEM), and energy-dispersive X-ray. XRD analysis detected the presence of rhombohedral crystalline phase in the doped samples sintered at different temperatures. FE-SEM and bulk density results confirmed that doping of the willemite with Eu2O3 effectively enhanced densification. The microstructural analysis of the doped samples showed that the average grain size increased with the increase of sintering temperature.